Development of Articulate Storyline-Based Interactive Media for Grade VIII Middle School Students on Vibrations and Waves - Setiawan, Agung Mulyo; Fitriana, Dewi Khajar (Universitas Negeri Malang, 2023)
Vibration and wave material in science subjects has several abstract concepts that make junior high school students' learning motivation low. One way to increase student learning motivation is to develop interactive learning media. This study uses the ADDIE model which consists of the stages of analysis - design - development - implementation - evaluation. The purpose of this research is to produce interactive media based on an Articulate Storyline on vibration and wave material that is valid, feasible, and able to motivate students to learn. The results of the interactive media that have been developed have the following content, namely, a) a description of the concept of vibration and wave material, b) the role of waves in various natural phenomena, c) a mathematical equation of the concept of vibration and waves. Then for the results of the expert validation test, our media was declared very valid with a percentage of 100% by material experts and 95.0% by media experts. Furthermore, from the results of the due diligence, our media obtained very appropriate criteria with a score of 96.2% by students and 98.0% by teachers. Meanwhile, from the results of the student learning motivation questionnaire after learning, our media obtained a percentage of 91.1% in the very good category. Therefore, it can be concluded that the interactive media based on Articulate Storyline that we developed on vibration and wave material for junior high school students is valid, feasible, and able to motivate students to learn.